Evaluación de la producción de una suspensión carbón-agua a nivel laboratorio como combustible para la empresa Industrias Magma S.A. (2016)
The formulation of a coal-water slurry fuel requires a set of process variables involved in the final characteristics of the fuel, so that a literature review concerning the most representative variables and from this analysis is possible are set raw materials and process conditions. Theoretical knowledge of raw materials (sodium hydroxide and citric acid) by comparing the advantages and disadvantages in terms of cost and availability are select. Process are chosen taking into account that reported in various literature sources, where finally the coal and additive concentration and the type of additive represent the object of study in the preparation of CWS.